The prevalence of anaemia among males and females in rural Bangladesh - Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
This is the first report of a collaborative research project between the Research and Evaluation Division (RED), BRAC, Bangladesh and the Department of Epidemiology and Public Health, Umea University, Sweden. The study aimed at investigating the prevalence · of anaemia among men and women in a typical Bangladesh rural community. The survey was conducted in a perceived healthy population in March 1996 in 12 villages of Fulbaria Thana of Mymensingh District located about 1 00 km north of Dhaka city. One hundred and six males 228 non-pregnant females aged 11-48 years were purposively selected. Information was obtained on haemoglobin concentration, parasitic infestation and household socio-economic status. About 69% of males and 70% of females were found to be anaemic according to WHO anaemia criteria. There was no difference in anaemia prevalence between males and females. Literacy and perceived economic status were associated to anaemia prevalence among females, but not among males. Anaemia was also more common among those holding little or no land and among those having current ascaris infestation. The study suggests that anaemia is highly prevalent in the rural communities of Bangladesh which affects both males and females equally. Further studies should be undertaken to confirm the findings and also to examine the causes of anaemia both in males and females in the rural areas of the country in order to undertake necessary preventive and control measures by the concerned agencies.